2005
DOI: 10.1210/jc.2004-1831
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Citrate (Viagra) Enhances Vasodilatation in Fetal Growth Restriction

Abstract: We conclude that sildenafil citrate improves endothelial function of myometrial vessels from women whose pregnancies are complicated by intrauterine growth restriction. Sildenafil citrate may offer a potential therapeutic strategy to improve uteroplacental blood flow in FGR pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(105 citation statements)
references
References 38 publications
3
101
0
1
Order By: Relevance
“…In FGR and PET, there is decreased depth and density of trophoblast invasion 6,7 and myometrial small arteries show increased vasoconstriction and decreased endothelium-dependent vasodilatation. 8,9 Vascular endothelial growth factor is essential for angiogenesis during development. 10 Vascular endothelial growth factor (VEGF) gene or protein therapy may prove therapeutically useful in local perivascular applications by stimulating vascular-protective endothelial functions.…”
mentioning
confidence: 99%
“…In FGR and PET, there is decreased depth and density of trophoblast invasion 6,7 and myometrial small arteries show increased vasoconstriction and decreased endothelium-dependent vasodilatation. 8,9 Vascular endothelial growth factor is essential for angiogenesis during development. 10 Vascular endothelial growth factor (VEGF) gene or protein therapy may prove therapeutically useful in local perivascular applications by stimulating vascular-protective endothelial functions.…”
mentioning
confidence: 99%
“…Again, this agrees with our work. Also, Lin et al [21] reported a decrease in uterine artery pulsatility and resolution of uterine artery notching following administration of sildenafil citrate to a case of IUGR diagnosed at 26 weeks of gestations. Contradictory to our findings, they also observed increase in EFW without maternal or neonatal adverse outcomes.…”
Section: Statistical Analysis Of the Datamentioning
confidence: 99%
“…Because of the importance of placental blood flow to placental function, and the recognition that placental size, uteroplacental blood flows and angiogenesis, and expression of angiogenic and vasoactive factors are reduced or altered in compromised pregnancies, it has been suggested that therapeutic agents that target placental blood flow and vascular development could be used to ameliorate fetal growth restriction (Godfrey, 2002;Ahmad and Ahmed, 2005;Wu et al, 2004;Wareing et al, 2005;Reynolds et al, 2006).…”
Section: 'Rescue' Of Placental Angiogenesis and Blood Flow In Comprommentioning
confidence: 99%